Innovation metrics: A critical review - Lyubomir Todorov; Margarita Shopova; Iskra Marinova Panteleeva; Lyubomira Todorova (Economies, 2024)
Innovations are complex phenomena with important impacts on firms, regions, the economy as a whole, society, and the environment. Measuring innovation is a challenging and time-consuming task with many problems ranging from the conceptual framework to data collection and interpretation. The development of the produced variety of single indicators and multidimensional metrics covers one or more innovation characteristics - inputs, stages, sources, mechanics, outputs, and impacts. While the abundance of metrics allowed measurement of many innovation aspects, it also created problems with comparability, coverage, timeliness, and reliability, making it difficult for academics, businesses and policymakers to efficiently use the information, perform correct analysis and make adequate decisions. To address this problem, this article aimed to review the literature, develop instruments for the structuring and assessment of the innovation measurements, systematize the variety of metrics, and evaluate their compliance with the requirements of users' needs and the quality of statistical information. The literature review identified 23 innovation metrics and helped create a classification scheme with 11 attributes and a criteria checklist with seven criteria groups. The results from the application of the instrument for the identified metrics revealed that they could be divided into three groups: appropriate, needing refinement, and unsuitable, with the best ones being the European Innovation Scoreboard and Global Innovation Index. They too showed some data gaps, connected with cultural environment, sustainability, open innovations, structural changes, and regional development, thus reinforcing the necessity for further advancement of theory and methodology for innovation measurement to augment the high-quality macro-information that is readily available with firm-level qualitative data of the innovation at the place where they emerge.
Keywords: 330; innovation metrics; innovation measurement; innovation indicators; comparative analysis